Antimicrobial activity of various brands of children's toothpastes formulated with Triclosan, Fluoride and Xylitol - Cosme-Silva, Leopoldo; da Silveira, Ana Paula Pereira; Gasque, Kellen Cristina da Silva; Moretti Neto, Rafael Tobias; Sakai, Vivien Thiemy; Moretti, Ana Beatriz S (Brazilian Dental Science, 2019)
Objective: Evaluate and compare the antimicrobial efficacy of four different commercially available children’s toothpastes on bacteria growth inhibition from oral microbiota of young children. Material and Method: The toothpastes tested contained: 1100 ppm sodium fluoride, xylitol and 750 ppm sodium fluoride, xylitol and 500 ppm sodium fluoride, and  xylitol and triclosan. Twenty 18 to 30 month-old children were selected. Nonstimulated saliva samples were collected and inoculated on brain heart infusion (BHI) agar. Toothpaste dilutions were applied into the agar wells and incubated at 37ºC for 24 hours in microaerophilic conditions. Saline and 0.12% chlorhexidine were used as controls. Antimicrobial activity was determined in duplicate by agar-well diffusion technique. Bacterial growth inhibition zones were recorded in mm. Statistical analysis was performed using ANOVA and Tukey's test (p